THE THEME OF THE ARMENIAN GENOCIDE IN THE IRANIAN DISCOURSE - Mkrtchyan, Karen (Armenian Folia Anglistika, 2025)
The theme of the Armenian Genocide in Iranian discourse has been significantly influenced over decades by various factors, including events organized by the Armenian community itself, as well as scholarly works such as monographs and studies authored by Iranians. In this article, we explore how responses to the commemoration of the 85th to 92nd anniversaries of the Armenian Genocide have shaped the narrative within the Iranian discourse, preceding and following the 90th anniversary. The Armenian community in Iran has actively contributed to this discourse through organizing events commemorating the genocide. These events serve not only as memorials but also as platforms for educating Iranian society at large about the historical realities and implications of the genocide. Additionally, Iranian authors have made contributions to the academic understanding and discussion of the Armenian Genocide through their scholarly works. Monographs and individual studies by Iranian researchers have provided insights into various aspects of the genocide, including historical contexts, political implications, and cultural repercussions. The responses to the anniversaries of the Armenian Genocide in Iran reflect evolving attitudes and perspectives over time. From initial silences and denials to more open acknowledgments and discussions, the discourse within Iranian speech has seen shifts influenced by both internal and external factors.
Keywords: Armenian Genocide; Iranian speech; Armenian community of Iran; Parliament; deputy; anniversary; commemoration ceremony